Pengaruh Perlakuan Alkali Pada Serat Agave dan Ketebalan Inti Terhadap Kekuatan Bending dan Impak Komposit Sandwich Serat Agave-Polyester dengan Inti Kayu Olahan (Engineering Wood) - Ferriawan Yudhanto (Jurnal Teknoin, 2015)
Fiber and synthetic core as a component of composite sandwich proved costly and not environmentally. Natural of Indonesia resources are very abundant natural materials. Human resources in Indonesia are still need a lot of land to work. Back to nature is a smart step and wise for the condition. Innovation of the natural material made to eliminate weaknesses in their mechanical properties. Engineering Wood can be used as a core of composite sandwich is particles board. This research discusses the manufacture of composite sandwich with skin of agave or sisal fiber (random distribution) and core of composit sandwich is particle board. Variable thickness of the core used are 10 mm and 15 mm. The process of making the sandwich composite engineering wood core is made through compression molding process of pressing the composite mold. Alkali treatment of agave fibre at 2 % concentration NaOH solution for 2 hours.. Result of testing material (Bending and Impact) showed a sandwich composite with a core thickness of 10 mm has a brittle compared to the core composite sandwich 15 mm which has a ductile mechanical properties. These results are shown from the increase in the deflection bending test is equal to 1,5 mm to 2,75 mm without alkali treatment (up 83%) and 2 mm to 3 mm with alkali treatments for 2 hour (up 50%). Impact testing material results obtained is 0,007 J/mm2 at core 10 mm and 0,009 J/mm2 at core 15 mm (up 28,5%) for core thickness variations. Value of ductility material raise result obtained is 0,012 J/mm2 (up 70%) at core 10 mm and 0,013 (up 44%) at core 15 mm with alkali treatments for 2 hours. The macro fracture from testing material can be concluded that the sandwich composite materials are brittle will have the form of shear fracture while the ductile will have the form of delamination skins and core on the interfacial bonding and fiber pull out.